Dielectric Resonator Direction Finding Antenna - Laila Hady Salman; Darko Kajfez; Ahmed A. Kishk (International Journal of Antennas and Propagation)
The idea of using a cylindrical dielectric resonator antenna for mechanical direction finding and target tracking is presented. The hybrid feeding network of the receiving antenna comprised two ports: one for the broadside-type sum pattern and another for the monopole-type difference pattern. The proposed design is fabricated and tested experimentally for concept validation. Both linearly polarized patterns were obtained around 2.6 GHz. The coupling between the sum and difference ports is measured to be smaller than −30 dB, and the 3 dB width of the minimum in the difference pattern is 10°.